Quality measures of clinical pharmacy services during transitions of care. Issue 7 (14th July 2021) - King, Philip K.; Burkhardt, Crystal; Rafferty, Aubrie; Wooster, Jessica; Walkerly, Autumn; Thurber, Kristina; Took, Roxane; Masterson, Jordan; St. Peter, Wendy L.; Furuno, Jon P.; Williams, Evan; Ferren, Janie; et al.
Abstract: The impact of clinical pharmacy transitions of care (TOC) services on relevant quality measures (QMs) has been a major focus in the recent biomedical literature. The 2020 ACCP Transitions of Care Task Force was charged with updating a 2012 white paper that focused on process indicators of quality clinical pharmacy services during TOC. The Task Force extensively reviewed the recent literature and regulatory measures relevant to TOC services. Given the wide heterogeneity and apparent uncertainty in these measures, the Task Force identified a need to define broader groupings for QMs so that pharmacy TOC services could more be reliably compared across various institutions and practice settings. The Task Force recommends QMs for the processes used to identify, and ultimately resolve, medication discrepancies (QM‐1) and medication therapy problems (MTPs) (QM‐2). Although interventions through various processes can be used to resolve medication discrepancies and MTPs, the findings of these interventions are closely aligned with the major outcomes from these TOC services. Therefore, the Task Force strongly recommends that the successful resolution of medication discrepancies and MTPs be studied for their potential roles as intermediate, or surrogate, QMs (iQM‐1, iQM‐2, respectively) because these are most likely to directly influence or predict quality related to major outcomes from TOC services. In addition, three QMs related to major outcomes are recommended, which are consistent with the triple aim: QM‐3: Health Care Utilization (HCU), QM‐4: Satisfaction and Engagement, and QM‐5: Economics. QM‐3, QM‐4, and QM‐5 span patient‐centered outcomes to institutional, or clinician‐based, outcomes. Specific metrics used for each QM are recommended. In addition to highlighting confounding variables affecting findings in the recent literature, broader contextual considerations that may support TOC services or span multiple practice settings are summarized. Future studies must adopt standard QMs and seek to understand the potential of iQMs to accurately predict success within major patient‐centered and institutional outcomes.